The occurence of cocaine in Egyptian mummies: new research provides strong evidence for a trans-Atlantic dispersal of humans - Görlitz, Dominique (Diffusion Fundamentals, 2016)
One of the unsolved problems of modern science is whether the pre-Columbian peoples of the New World developed completely independently of cultural influences from the Old World or if there was a trans-oceanic contact? A number of scientists agree that there are many – and often remarkable – similarities between the cultures of pre-Columbian America and those of the Mediterranean world. Nevertheless, there is no agreement, as yet, on how cultural diffusion can be differentiated from independent invention. Scientific analysis shows that scholarly positions are often strongly pre-formed from paradigms (scientific based assumptions), which tend to hinder consideration of solid scientific data offered by geo-biology and its trans-disciplinary examination of the subject under investigation here. An unambiguous answer to the question, what historical processes led to the emergence of the ancient American agriculture, hasn''t been given. However, the archaeological discovery of crops with clear trans-oceanic origin, in addition to advances in molecular biology, increasingly support the hypothesis that humans from the distant past influenced each other across the oceans at a much earlier stage. The vegetation and zoo-geography indicate, by numerous examples that some species could only have spread through perhaps unintentional (passive) human transmission [1]. There are two very old crops found in the „New World‟, which contradict the paradigm of a completely independent origin for American agriculture. These are the African Bottle Gourd (Lagenaria siceraria L.) and the ancestral cotton species (Gossypium herbaceum L.) of the domesticated spin able sub-genus of tetraploid cotton. The historical spread of both types has been under discussion for decades, especially in respect of trans-oceanic human contact with the American continent. There has also been a debate in the "Old World" ever since the discovery of nicotine and cocaine in Egyptian mummies, centering around whether "New World" plants (or the ingredients) might have been transmitted in the reverse direction, back to the presumed start in centers of the Ancient World''s oldest civilizations.